Effect of Garlic Powder (Allium sativum) on Blood Constituents in Male Rabbits - Al-Jowari, Suha Abdul-khaliq (Al-Nahrain Journal of Science, 2018)
The effect of garlic powder on blood constituents in male rabbits was studied. These constituents were hemoglobin concentration, packed cell volume, red blood cell count, total and differential white blood cell count, platelets count and red cell indices. Fifteen male rabbits were randomly divided into three groups (five animals in each group). Two groups were supplied with pellets containing 1 and 5% garlic powder. The last group was considered as control and supplied with pellets and water. The period of experiment was lasted for 21 days. The results showed that there was a significant (P≤0.05) increase in the means of hemoglobin concentration, packed cell volume, platelets count, total white blood cells count, lymphocytes count, neutrophils count and mean corpuscular hemoglobin concentration in the group treated with 5% garlic powder compared with control group, while, there was no significant differences in these mentioned parameters at the treated group with 1% garlic powder compared with control group. In addition, there was a significant (P≤0.05) increased in red blood cells count at 1% and 5% garlic powder compared with control group. On the other hand, there were no significant differences in the means of monocytes count, eosinophils count, basophils count, mean corpuscular hemoglobin and mean cell volume in the treated groups with 1% and 5% garlic powder compared with control group.